1998
DOI: 10.1038/3511
|View full text |Cite
|
Sign up to set email alerts
|

Expression and inheritance of multiple transgenes in rice plants

Abstract: The ability to control integration, inheritance, and expression of multiple transgenes is a prerequisite for manipulating biosynthetic pathways and complex agronomic characteristics in plants. One hundred and twenty-five independent transgenic rice plants were regenerated after cobombarding embryogenic tissues with a mixture of 14 different pUC-based plasmids. Eighty-five percent of the R0 plants contained more than two, and 17% more than nine, of the target genes. Plants containing multiple transgenes display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(107 citation statements)
references
References 23 publications
(27 reference statements)
6
101
0
Order By: Relevance
“…The tendency of multiple DNA molecules, derived from the cotransformation of several different Agrobacterium strains or from cobombardment of several plasmids, to integrate into the same genomic locus (De Neve et al, 1997) has been utilized as a viable method for the production of single-locus multigene transgenic plants (for review, see Naqvi et al, 2010;Peremarti et al, 2010). While this approach has been successfully used to produce transgenic plants in which up to 11 transgenes are cointegrated into the same locus (Chen et al, 1998;Zhu et al, 2008;Naqvi et al, 2009), it is impossible to predict the physical organization and the arrangement of cotransformed DNA molecules in the transgenic plants. Indeed, it has been suggested that future progress in multigene transformation may depend not only on driving the transgenes under the specific combinations of promoter and terminator sequences but also on organizing the transgenes in a predetermined pattern (Peremarti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The tendency of multiple DNA molecules, derived from the cotransformation of several different Agrobacterium strains or from cobombardment of several plasmids, to integrate into the same genomic locus (De Neve et al, 1997) has been utilized as a viable method for the production of single-locus multigene transgenic plants (for review, see Naqvi et al, 2010;Peremarti et al, 2010). While this approach has been successfully used to produce transgenic plants in which up to 11 transgenes are cointegrated into the same locus (Chen et al, 1998;Zhu et al, 2008;Naqvi et al, 2009), it is impossible to predict the physical organization and the arrangement of cotransformed DNA molecules in the transgenic plants. Indeed, it has been suggested that future progress in multigene transformation may depend not only on driving the transgenes under the specific combinations of promoter and terminator sequences but also on organizing the transgenes in a predetermined pattern (Peremarti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This feature is important when large numbers of genes are considered, because a much larger transgenic population would be required if each integration event were independent (Altpeter et al, 2005). Chen et al, (1998) successfully transformed rice (Oryza sativa) plants by particle bombardment with 13 separate plasmids containing different marker genes, and regenerated plants carrying and expressing all the input genes at one locus. Subsequently, Wu et al, (2002) transformed rice with nine transgenes also by particle bombardment and found that nonselected transgenes were present along with the selectable marker in approximately 70% of the plants and that 56% carried seven or more genes.…”
Section: The Scope Of the Challengementioning
confidence: 99%
“…By co‐expressing multiple proteins, crops have been successfully modified to acquire enhanced abiotic tolerance, improved pathogenic resistance, as well as enriched nutritional contents (Arvinth et al ., 2010; Chen et al ., 1998; Sun et al ., 2012). Currently, only a limited number of approaches are available for co‐expression of multiple proteins in plants.…”
Section: Introductionmentioning
confidence: 99%